Multi-scale update on precipitation characteristics at Jinan, East China - Shufen Chen (IWA Publishing, 2021)
Extreme precipitation triggered by climate change is a hot issue of global concern. This study investigates changes in temporal trends of precipitation at Jinan City, Shandong Province over the last six decades. It first constructs a long series of measured daily precipitation data (1951–2017) and then exploits the relative variability, Mann–Kendall, and rescaled range analysis (R/S analysis) methods to update precipitation characteristics. Results indicate that: (1) annual precipitation varies over 116%, with 74.1% of total precipitation concentrated from June to September, especially for heavy rains and storm days; (2) at the 95% confidence level, the annual rainfall does not increase significantly (U = 1.15), but there is a significant upward trend in the spring (U = 2.08), whereas there is no significant downward trend in the fall (U = −1.03); (3) precipitation sequence mutates in 1990, consistent with spring precipitation series, while there are two to four mutations in summer, autumn, and winter. The above results will provide the theoretical basis and data support for the rational development of water resources in Jinan; meanwhile, studying the law of precipitation changes in Jinan City has important practical significance for flood disaster prevention. HIGHLIGHTS A latest measured long-sequence precipitation data set (over 60 years) is established;; Precipitation characteristics in Jinan are updated;; Annual precipitation varies over 116%, with 74.1% of total precipitation concentrated from June to September, especially for heavy rains and storm days;; Precipitation sequence mutates in 1990, consistent with spring precipitation series;; Future precipitation trends continue to increase.;